2020
DOI: 10.15406/ijh.2020.04.00256
|View full text |Cite
|
Sign up to set email alerts
|

Some important elements of soil-water relationship in managing oil palms planted on acid sulfate soils

Abstract: Oil palms (Elaeis guineensis) are generally able to grow economically and feasibly on various soil types, mostly in tropical countries. However, oil palms planted on acid sulfate soils were producing lesser Fresh Fruit Bunches (FFB) as compared to those on non-acid sulfate soils. The poor performance of oil palms planted on acid sulfate was mainly attributed to the presence of excess sulfates, which limits the FFB yields and vegetative growth.1 Generally, acid sulfate soils have significant amounts of free and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 2 publications
0
8
0
1
Order By: Relevance
“…[11] highlighted in their paper that ammonium-based nitrogen fertilizers in excess rates, leaching of nitrate nitrogen, and continual removal of plant & animal waste products could accelerate the change of pH. Many researchers highlighted that oil palm can tolerate well to low pH values in the range of 4 and 5 for commercial oil palm production especially in Southeast Asia [3,7,8,12]. [13] reported that (i) experiments carried out in four sites in Indonesia have shown that high yields are possible on soils with low pH and (ii) best management practices can increase pH.…”
Section: Influences and Changes Of Ph Valuesmentioning
confidence: 99%
See 4 more Smart Citations
“…[11] highlighted in their paper that ammonium-based nitrogen fertilizers in excess rates, leaching of nitrate nitrogen, and continual removal of plant & animal waste products could accelerate the change of pH. Many researchers highlighted that oil palm can tolerate well to low pH values in the range of 4 and 5 for commercial oil palm production especially in Southeast Asia [3,7,8,12]. [13] reported that (i) experiments carried out in four sites in Indonesia have shown that high yields are possible on soils with low pH and (ii) best management practices can increase pH.…”
Section: Influences and Changes Of Ph Valuesmentioning
confidence: 99%
“…[13] reported that (i) experiments carried out in four sites in Indonesia have shown that high yields are possible on soils with low pH and (ii) best management practices can increase pH. [3] also reported that a high FFB yield above 35 tons per ha per year is possible on acid sulfate soils with proper nutrient inputs as well as good water management.…”
Section: Influences and Changes Of Ph Valuesmentioning
confidence: 99%
See 3 more Smart Citations